2010
DOI: 10.1111/j.1349-7006.2010.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibitory effect of formestane and herceptin on a subpopulation of CD44+/CD24low breast cancer cells

Abstract: In breast cancer, stromal cells surrounding cancer epithelial cells can influence phenotype by producing paracrine factors. Among many mediators of epithelial-stromal interactions, aromatase activity is perhaps one of the best studied. Clinical data suggest that estrogen-independent signaling leads to increased proliferation even during therapy with aromatase inhibitors (AIs). Molecular mechanism of crosstalk between the estrogen receptor (ER) and the epidermal growth factor receptor (HER) family have been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Basal breast cancer cell line JIMT-1 which is HER2-positive, trastuzumab-refractory, ER-negative, and Vimentin-positive is a best cell model to explain the link between HER2, EMT and trastuzumab resistance. De novo resistance of JIMT-1 cells to trastuzumab can be explained by the emergence of trastuzumab-resistance BCSCs due to the dynamic interaction between HER2 and EMT [19,[38][39][40][41][42][43]. The subpopulation of CD44+/CD24-BCSC in the early culture of the JIMT-1 cell line is reported around 10%.…”
Section: Cd44+/cd24-cells Were Isolated By Facs From Non-tumorigenic mentioning
confidence: 99%
“…Basal breast cancer cell line JIMT-1 which is HER2-positive, trastuzumab-refractory, ER-negative, and Vimentin-positive is a best cell model to explain the link between HER2, EMT and trastuzumab resistance. De novo resistance of JIMT-1 cells to trastuzumab can be explained by the emergence of trastuzumab-resistance BCSCs due to the dynamic interaction between HER2 and EMT [19,[38][39][40][41][42][43]. The subpopulation of CD44+/CD24-BCSC in the early culture of the JIMT-1 cell line is reported around 10%.…”
Section: Cd44+/cd24-cells Were Isolated By Facs From Non-tumorigenic mentioning
confidence: 99%
“…Basal BC cell line JIMT-1 cells are HER2+, trastuzumab-refractory, ER−, and Vimentin+. The de novo resistance of JIMT-1 cell to trastuzumab can be explained by the emergence of trastuzumab-resistance BCSCs due to the dynamic interaction between HER2 and EMT [98,99,100,101,102,103,104]. JIMT-1 cell line is composed of approximately 10% CD44+/CD24− BCSC.…”
Section: Emt Drives Resistance To Trastuzumabmentioning
confidence: 99%
“…Treatment of CD44+/CD24− BCSCs derived from breast tumor tissues with formestane, an aromatase inhibitor, results in a 16% ( p < 0.01) decrease in cell proliferation in response to single-agent trastuzumab and 50% decrease ( p < 0.001) in response to combined trastuzumab and formestane treatment. The combined treatment also inhibits the expression of EGFR, HER2, Aromatase and Cyclin D1 in CD44+/CD24− cells, which suggests that targeting HER2 by trastuzumab may inhibit the growth of CD44+/CD24− BCSCs through the inhibition of cell cycle progression [101]. Some other reports suggest that preferential killing of the putative CD44+/CD24− BCSCs might be sufficient to overcome primary resistance to trastuzumab.…”
Section: Emt Drives Resistance To Trastuzumabmentioning
confidence: 99%
“…Studies to determine the effects of freeze and thaw on mammospheres derived from the MCF7 breast cancer cell line demonstrate that cryopreservation does not affect cellular proliferation and function but increases the rate of senescence mediated pathway (Karimi-Busheri et al 2010). Comparison of plates, media and supplements used to mammospheres formation from single cell suspension of tumor cells are reported on Table 1 (Dontu et al 2003;Ponti et al 2005;Fillmore and Kuperwasser 2008;Mani et al 2008;Klopp et al 2010;Cavaliere et al 2010). Widely used protocols of Dontu et al (2003) and Ponti et al (2005) are reported to be successful to propagate cancer stem cells on low or ultra low attachment surface of 6 or 24-well plates with cell dilutions ranging from 1 to 1,000 cells/mL.…”
Section: Mammospheresmentioning
confidence: 99%